Phylogenetic insights on the isoflavone profile variations in Fabaceae spp.: Assessment through PCA and LDA - Visnevschi-Necrasov, Tatiana (2018)
Legumes (Fabaceae) are important crops, known as sources of food, feed for livestock and raw materials for industry. Their ability to capture atmospheric nitrogen during symbiotic processes with soil bacteria reduces the need for expensive chemical fertilizers, improving soil and water quality. Several Fabaceae species are acknowledged for the high levels of secondary metabolites. Isoflavones are among the most well-known examples of these compounds, being recognized for their several types of biological activity. Herein, isoflavone profiles were characterized in nine species of four Fabaceae genera (Biserrula, Lotus, Ornithopus and Scorpiurus). Plants were harvested in the late flower physiological stage to prevent biased results due to naturally occurring variations along the vegetative cycle. Isoflavones were extracted using matrix solid-phase dispersion and analyzed by high performance liquid chromatography/diode-array detection. The detected profiles revealed significant differences, inclusively among species belonging to the same genus, indicating that other factors besides the genotypic features contribute to the expression of these phenolic compounds. The classification of the results by principal component analysis placed species belonging to the same genus in different clustering groups, proving this latter assumption. However, the detected profiles proved to be characteristic of the assayed, as it was proved by the applied linear discriminant analysis.